2006
DOI: 10.1017/s002211200600927x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of vortices shed from cylinders with a step-change in diameter

Abstract: The interactions of vortices shed from two coaxially joined cylinders with a diameter ratio of 0.51 have been studied in a water channel, at Reynolds numbers, based on the large cylinder diameter, between 63 and 1100. Spectral and wavelet analyses of streamwise velocity measurements have identified the formation of three distinct spanwise vortex-shedding cells away from the far ends of the two cylinders, including a low-frequency cell, which appeared in a cyclic manner near the step and behind the large cylind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
72
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 24 publications
17
72
0
1
Order By: Relevance
“…Despite differences in geometries, it has been shown that, in uniform flows, spanwise vortices are shed in constant-frequency cells in the wakes of cantilevered, 4,5 tapered, 6,7 and step cylinders. [8][9][10][11][12][13][14][15][16] The arrangement of the vortex cells and wake vortex interactions, however, have been shown to depend significantly on the geometry. For cantilevered cylinders, a lower frequency vortex shedding cell forms near the free end, 4 and a higher frequency cell, similar to vortex shedding in the wake of a uniform circular cylinder, is observed away from the free end.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite differences in geometries, it has been shown that, in uniform flows, spanwise vortices are shed in constant-frequency cells in the wakes of cantilevered, 4,5 tapered, 6,7 and step cylinders. [8][9][10][11][12][13][14][15][16] The arrangement of the vortex cells and wake vortex interactions, however, have been shown to depend significantly on the geometry. For cantilevered cylinders, a lower frequency vortex shedding cell forms near the free end, 4 and a higher frequency cell, similar to vortex shedding in the wake of a uniform circular cylinder, is observed away from the free end.…”
Section: Introductionmentioning
confidence: 99%
“…Vortex interactions within this region were the topic of several subsequent investigations. [9][10][11][12] Lewis and Gharib 10 identified two different modes of vortex shedding interaction, namely, the "direct mode" and the "indirect mode." In the direct mode ͑D / d Ͻ 1.25͒, the vortex interaction region is relatively narrow, with vortex connections occurring between vortices shed from the large and the small cylinders and vortex dislocations involving connections between vortices in the same cell.…”
Section: Introductionmentioning
confidence: 99%
“…These three-dimensionalities can induce significant spanwise variations in the velocity and pressure fields. In contrast, such three-dimensionalities are known to occur if the diameter of the cylinder changes discontinuously [2][3][4] or linearly [5][6][7][8][9][10][11][12][13][14] even at a Reynolds number well below the critical value Ϸ190. Almost all previous studies on the flow past linearly tapered circular cylinders are either in the laminar flow regime [5][6][7][8][9][10][11]15 or in the turbulent flow regime.…”
Section: Introductionmentioning
confidence: 99%
“…One result is that the recirculation near a step has significant effects on the shedding frequencies as compared to locations away from the step. Similarly, another study from Dunn et al [10] also found significant effects of free-stream shearing on vortex-shedding characteristics from a step-cylinder. Chris Morton et al [11][12][13][14][15][16] carried out several studies using both numerical and experimental with 2D and 3D particle image velocimetry (PIV) investigations on step cylinders, such as single step dual step, etc.…”
Section: Introductionmentioning
confidence: 72%
“…N.Ko et al [19] 8 × 10 4 2 Yagita et al [20] 8 × 10 2 -10 4 1.25-5 Lewis et al [21] 67-200 1.14-1.76 Dunn et al [10] 62-1230 2 Norberg [22] 3 × 10 3 -13 × 10 3 1.25-2 N. Ko et al (1984Ko et al ( , 1990Ko et al ( , 1992 [23][24][25] 8 × 10 4 1.33-2.78 Chua et al [26] 4.72 × 10 3 3 Morton et al [11,27,28] 150-2100 2 Dunn et al [9] (span-wise sheared flow) 152-764 1.92…”
Section: Re D D/dmentioning
confidence: 99%